Rural income diversification in Ethiopia: Patterns, trends, and welfare impacts - Abate, Gashaw T.; Bachewe, Fantu Nisrane; Regassa, Mekdim D.; Minot, Nicholas (International Food Policy Research Institute, 2022)
Increased diversification of rural households into the rural non-farm economy is an important driver of economic growth and structural transformation in countries like Ethiopia where most people live in rural areas and are largely dependent on seasonal agriculture. In this study, we explore the patterns and trends of diversification and assess its drivers and welfare effects during the recent decade (2012 – 2019) using three rounds of representative household data collected from four major regions in Ethiopia. Our results show that sample households generally adopt a livelihood strategy dominated by farming and that the level of diversification has been stagnant over the period of analysis considered. More importantly, most households continue to draw a substantial share of their income from crop production, followed by livestock. The income from non-farm activities accounts only between 17-23% of the total household income. Upon exploring the link between diversification and welfare outcomes, we find that households with relatively diversified income sources have significantly higher consumption expenditure per capita, consume diverse diets, and live in house with better roof quality. Further analyses reveal that income diversification is positively associated with credit access, membership in social insurance, ownership of assets and wealth, and population density. Conversely, access to relatively large, fertile, and irrigable land discourages diversification. In sum, the results imply the need for a deliberate effort to expand the non-farm economy to tap its full potential for employment generation, income growth, and overall welfare improvements.